Enhancing the Biocatalytic Activity of l -Asparaginase Using Aqueous Solutions of Cholinium-Based Ionic Liquids - Magri, Agnes [UNESP]; Pecorari, Thainá [UNESP]; Pereira, Matheus M.; Cilli, Eduardo M. [UNESP]; Greaves, Tamar L.; Pereira, Jorge F. B. [UNESP] (American Chemical Society (ACS), 2019)
l-Asparaginase (ASNase) is a high value enzyme for the pharmaceutical and food industries. Although ionic liquids (ILs) have been recognized as promising solvents or additives for biocatalysis, there are very few studies on the effect of ILs on the activation of ASNase. To address this, the enzymatic activity of a commercial ASNase in aqueous ILs was evaluated. ASNase was exposed for up to 24 h to aqueous solutions (0.001-0.050 mol·mol-1) of cholinium ([Ch])-based ILs, at three temperatures (25, 37, and 50 °C). At 25 °C, [Ch]-based IL aqueous solutions enhanced the biocatalytic activity of ASNase, with a maximum increase of the relative ASNase activity (of ca. 250%) achieved by adding cholinium chloride ([Ch]Cl). Spectroscopic and calorimetric analyses were performed to understand the effect of [Ch]Cl on the ASNase structure, but no significant changes were observed. Although all [Ch]-based ILs enhanced the relative ASNase activity, the positive effects were diminished with increasing the anion alkyl chain length, i.e. from acetate to hexanoate. The increase of temperature to 50 °C caused a negative effect in the catalytic behavior of ASNase, leading, in most cases, to ASNase inactivation. Overall it was evident that [Ch]-based ILs are highly efficient biocatalytic additives to enhance ASNase activity in water (a 2-fold increase by adding less than 0.050 mol·mol-1). This simple and useful approach can be applied to increase the sustainability of several ASNase biocatalytic applications, especially in food processes.
Keywords: Asparaginase; Biopharmaceutical; Choline; Enzyme; Ionic liquids